The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1248/bpb.b13-00180
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Secretory Sphingomyelinase Activity and Specific Ceramides in the Aorta of Apolipoprotein E Knockout Mice during Aging

Abstract: Atherosclerosis is caused by many factors, one of which is oxidative stress. We recently demonstrated that systemic oxidative stress increased secretory sphingomyelinase (sSMase) activity and generated ceramides in the plasma of diabetic rats. In addition, we also showed that the total ceramide level in human plasma correlated with the level of oxidized low-density lipoprotein. To investigate the relationship between ceramide species and atherogenesis during aging, we compared age-related changes in ceramide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
2
18
1
Order By: Relevance
“…Hu et al ( 17 ) reported that STs were the only factor that discriminated control from ESRF groups in their study, and that they have promise as biomarkers for CKD. We observed a decrease in the level of Cer's in LDL from CKD patients; however, as increased sphingomyelinase activity and free Cer's are thought to be linked to atherogenesis ( 48,49 ), this does not appear to contribute to the proatherogenic profi le of CKD. Finally, it was also noted that there was a signifi cant increase in N-acyltaurines (NATs) in LDL from CKD patients.…”
Section: Discussionmentioning
confidence: 55%
“…Hu et al ( 17 ) reported that STs were the only factor that discriminated control from ESRF groups in their study, and that they have promise as biomarkers for CKD. We observed a decrease in the level of Cer's in LDL from CKD patients; however, as increased sphingomyelinase activity and free Cer's are thought to be linked to atherogenesis ( 48,49 ), this does not appear to contribute to the proatherogenic profi le of CKD. Finally, it was also noted that there was a signifi cant increase in N-acyltaurines (NATs) in LDL from CKD patients.…”
Section: Discussionmentioning
confidence: 55%
“…While neutral sphingomyelinase levels are unchanged in the liver and kidney, plasma S-ASM activity increases. These findings suggest that the induction of diabetes increases plasma ceramide levels by enhancing S-ASM activity (Kobayashi et al, 2013).…”
Section: S-asm In Diabetesmentioning
confidence: 71%
“…Irradiation induces increases in S-ASM activity in some but not all tumor patients, and a positive correlation between S-ASM activity and serum ceramide concentration has been observed (Sathishkumar et al, 2005). In rodents, increasing age is associated with increased S-ASM activity and a simultaneous increase in the concentration of individual ceramide species (Kobayashi et al, 2013). Other in vivo studies did not report the expected relationship between S-ASM activity and sphingolipid concentrations.…”
Section: In Vivo Effects Of S-asm Activity On Sphingolipid Levelsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, we previously found that levels of CSF very long chain ceramides with chain lengths of C20–C26 were higher in APOE E4 carriers compared with noncarriers (Mielke et al ., 2014). Further, studies of Alzheimer (Bandaru et al ., 2009) and HIV dementia brains (Cutler et al ., 2004) and aortic tissue levels of APOE knockout mice (Kobayashi et al ., 2013) have found APOE genotype alters ceramide levels in these compartments. Thus, the relationship between ceramides and APOE genotype likely varies depending on the compartment and disease state.…”
Section: Discussionmentioning
confidence: 99%